Therapeutic Spectrum of GLP-1 Receptor Agonist: From Glycemic Control to Metabolic Protection - Kamińska, Marta; Kotlarz, Wiktoria; Kuczma, Matylda; Klimczak, Adrianna; Pietrzak, Barbara; Patelski, Mikołaj; Czapla, Maciej; Surma, Mateusz; Mikusek, Wiktoria; Molenda, Jakub (Quality in Sport, 2026)
Introduction. Type 2 diabetes mellitus (T2DM) and obesity are major global health challenges. They are associated with cardiovascular, renal, and metabolic complications. Traditional therapies primarily target glycemic control but do not fully prevent long-term complications. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have emerged as multi-organ protective agents, offering benefits beyond glucose lowering. Aim of the study. This review provides a comprehensive overview of GLP-1 RAs. It covers their pharmacology, glycemic control, obesity management, cardiovascular and renal protection, safety profile, and emerging therapeutic indications. The objective is to highlight their therapeutic potential and support clinicians in individualized treatment planning. Materials and methods. This narrative review is based on a structured literature search conducted in PubMed and Google Scholar up to September 2025, using the following terms: GLP-1 receptor agonist, type 2 diabetes, obesity, cardiovascular outcomes, renal outcomes, weight loss, and neuroprotection. Additional relevant articles were identified through manual review of reference lists from key publications. Conclusion. GLP-1 RAs represent multifaceted therapeutic agents that improve glycemic control, induce significant weight loss and confer cardiovascular and renal protection. They are generally well tolerated, with gastrointestinal effects being the most common adverse events. Individualized therapy and ongoing research into novel agents and combination strategies may further enhance clinical outcomes in patients with T2DM, obesity, and cardiometabolic risk.